Address Terms Used by Local People in Menyali Village - Gede Bagus Kresnantara; I Gede Budasi; Ni Putu Astiti Pratiwi (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
The use of greeting terms in each region is different and this is influenced by social factors. This is a recent phenomenon that is interesting for further research. This study was aimed to analyze the types of address terms used in Menyali village and the social factors which influenced those address terms. Descriptive qualitative was used as the method of this study. The data were collected by conducting observation and interview through the use of observation sheet and interview guide as the instruments. There were three local villagers involved as the informants of this study. They were selected by using purposive technique sampling. The collected data were analyzed by using qualitative data analysis through data reduction, data display, and conclusion drawing. The findings showed that; 1) there were twelve types of address terms spoken by people in Menyali village; kinship terms, special nicknames, pet names, title only, first names, intimacy names, respect names, mockery names, pronouns, occupational terms, religious terms, zero address terms, 2) there were seven social factors influenced the address terms used in Menyali village; sex, family relationship, occupational hierarchy, age, social status, the official position of the interlocutor as the second person, and ethnicity.